'Supportive Parenting', Responsibility and Regulation: The Welfare Assessment under the Reformed Human Fertilisation and Embryology Act (1990). Issue 3 (May 2015) - Sheldon, Sally; Lee, Ellie; Macvarish, Jan
<x xml:space="preserve">Abstract</x> Section 13(5) of the Human Fertilisation and Embryology Act 1990 requires fertility clinics, before offering regulated treatment services, to take account of the welfare of any child who may be born as a result of the treatment and any other child affected by that birth. This paper presents the findings of an empirical study examining the impact on practice of the controversial reform of this section in 2008. While the broad values underpinning section 13(5) appear well embedded in clinic staff's engagement with ethical issues, there is little evidence that practice has been influenced by the 2008 amendments. A complex picture emerged regarding the implementation of section 13(5), particularly in its interaction with other factors, such as funding criteria and professional norms around counselling, implying a higher level of ongoing attention to likely parenting ability – particularly that of single women – than might be expected from a reading of the statute and guidance alone.